University Students’ Attitude Towards Artificial Intelligence: Scale Validation for Honduras - Reyes Flores, Luis Gerardo; Mejía Rivera, Kevin Arnaldo; Sorto Rojas, Edgar Fernando; Barahona Martínez, Cristhian Eduardo (LACCEI, 2025)
Abstract– Artificial intelligence (AI) is rapidly transforming various fields, including education, by offering new tools that can revolutionize teaching and learning. This article analyzes attitudes toward AI, as well as the challenges and opportunities it presents. As AI expands, its use in education has generated both hope and concern, necessitating regulations to govern its application, especially in higher education. Methods, this study focuses on adapting the SATAI (Student Attitude Toward Artificial Intelligence) scale in a Honduran context, using an incidental sample of 217 university students from the Central American Technological University (UNITEC). The study follows a quantitative, cross-sectional, and non-experimental approach, aiming to explain the relationship between students’ attitudes toward AI and their cognitive, affective, and behavioral characteristics. The results include an adaptation of the SATAI scale, with a reliability score of 0.88 and a KMO of 0.89, proposing a reduced 16-item version that demonstrated good performance based on goodness-of-fit statistics. Findings indicate a favorable attitude toward AI (3.6 out of 5), particularly in academic and entertainment contexts, highlighting the importance of teacher training for the ethical and effective use of these technologies. The discussion emphasizes the need for continued research on the relationship between AI and education, considering the potential long-term ethical and moral implications. This study contributes to the understanding of how AI is integrated into educational settings.